2016
DOI: 10.11113/jt.v78.9886
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Existing Two Stage Anaerobic Digestion Process for Palm Oil Mill Wastewater

Abstract: This work is an attempt to describe the dynamics of a two-stage industrial biogas plant using palm oil mill effluent (POME) and the mixture of POME with effluent from rubber factory (LTE), both at steady state and transient peroid before system failure accurred. One incident occurred in POME treatment plant when LFE bypassed its digesters and mixed together with palm-oil-mill wastewater due to no space in the existing latex wastewater ponds under water flooding during heavy raining period. The model was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…It was found that the plant failed within 75 days of operation. It was observed that after 60 days of co-digestion, the pH dropped sharply, and the plant started to fail irreversibly [19]. Thus, it is anticipated that the optimum/synergistic POME: LTE ratio (> 0.5) found in this work may not be applied directly to the continuous system with prolonged operation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was found that the plant failed within 75 days of operation. It was observed that after 60 days of co-digestion, the pH dropped sharply, and the plant started to fail irreversibly [19]. Thus, it is anticipated that the optimum/synergistic POME: LTE ratio (> 0.5) found in this work may not be applied directly to the continuous system with prolonged operation.…”
Section: Discussionmentioning
confidence: 88%
“…It was found that the plant failed within 75 days of operation. The failure dynamics of the incident was not clear, but it was observed that after 60 days of co-digestion, the pH dropped sharply, and the plant started to fail irreversibly [19].…”
Section: Introductionmentioning
confidence: 99%
“…Biogas plants from POME are relatively stable, easy to start-up and control, thus providing an excellent co-digestion platform. Different kinds of animal dung [ 22 ], rubber-latex effluent, aerobic and anaerobic sludges were used to co-digest with POME to improve C/N balance and provide richer trace elements [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…POME's anaerobic digestion modeling is currently somewhat limited, but research in this field is expanding rapidly in recent years [ 23 , 24 , 25 , 26 ]. Ramadhani et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation